Modelagem e simulação numérica do transporte de poluentes em meios porosos com reação química - Silva, André Luiz da (2016)
Currently there is a great concern for groundwater contamination due to environmental pollution. Because of the need to deal with problems of this nature, it is necessary to develop research to enable understanding of the spread of pollutants in porous media motivating the need to develop mathematical models and computer codes to simulate reactive transport multispecies pollutants. This work aimed to propose a mathematical model for the numerical simulation of the spread of pollutants in the saturated region of the soil, considering the advection mechanisms, diffusion, sorption and chemical reaction. The mathematical model obtained was discretized using the method of finite volume. The results show that the method of Finite Volume, presented a very satisfactory performance in the discretization of pollutant reactive two-dimensional transport problem of the conservation equations in groundwater, the numerical method was compared to a semi-infinite medium getting good results, simulated experimental design guided the work results. It also highlighted the good performance of the computer language as a support tool for the evaluation of environmental impacts caused by pollution sources, and you can view the extent and behavior of a plume of contamination and carry out numerous transactions in short time at low cost and producing results very close to reality.